Problems solution of global urbanism in the context of cultural development, technology and the formation of creative class - Voronkova, V. G.; Nikitenko, V. O.; Oleksenko, Roman; Олексенко, Роман Іванович; Олексенко, Роман Иванович (My University, 2020)
EN: In the article the structural and functional model of the city' cultural urbanization was developed in the context of the complexity methodology as the basis for solving the problems of the urban crisis, in which all countries and peoples of the world are involved. The analysis methodology is the use of systematic methods of structural and functional, informational and cultural analysis, as well as the complexity methodology as a basis for overcoming the urban crisis of urban agglomerations that are involved in the system of global urbanism and require solving the problems of urban life, middle creative class formation, increasing the global creativity index. The leading approach to the study of this problem is a complexity methodology, which includes a non-linear methodology, in the context of which the problems of global urbanization are solved. The urban crisis and ways of solving the problems of global challenges of agglomerations or large cities have been studied. The essence of the urban crisis and the problems of global challenges of agglomerations or large cities are presented. The problem of urban research is that modern cities were colonized by rich and successful people, leaving far behind the inhabitants of small villages and townships: hubs, covorkings and high-tech innovations have absorbed parks, stores and coffee shops; restructuring of cities and urban areas has led to increased rents and concentration of wealth in one hands. It has been established that under the global challenges of our time, high-tech agglomerations (megacities) are becoming the focus of all problems - economic, social, cultural, demographic, environmental. An attempt was made to divide urban agglomerations into 4 groups of cities and find out their problems. Megacities as epicenters of the economy suffer from economic splits, split into small areas of rich and large zones of poor areas. The problematic issues of the structural and functional model of the cultural urbanism of the city, which aims to bring global urbanism to a new level of technical, social and cultural progress and social development, have been identified. The prospects of solving the problems of global urbanization in the context of the development of the concept of Enlightenment 2.0 and the Fourth Industrial Revolution are analyzed. UK: У статті розроблено структурно-функціональну модель глобального урбанізму у контексті методології складності як основи вирішення проблем урбаністичної кризи, в яку втягнуті всі країни і народи світу. Методологія аналізу – використання методів системного, структурно-функціонального, інформаціологічного, культурологічного аналізу, а також методології складності як основи виходу з урбаністичної кризи міських агломерацій, які втягнуті у систему глобального урбанізму і вимагають вирішення проблем міського життя, формування середнього креативного класу, підвищення глобального індексу креативності. Провідним підходом до дослідження даної проблеми є методологія складності, до якої відноситься і нелінійна методологія, у контексті якої здійснюється вирішення проблем глобального урбанізму. Досліджена урбаністична криза і шляхи вирішення проблем глобальних викликів агломерацій чи великих міст. Представлено аналіз урбаністичної кризи та проблем глобальних викликів агломерацій чи великих міст. Проблематика дослідження урбанізму міст зводиться до того, що сучасні міста в США та Західній Європі колонізували багаті та успішні люди, залишивши далеко позаду жителів маленьких сіл і селищ: стали розвиватися аби, коворкінги і хай-тек-інновації, які поглинули парки, магазини і кофейні; перебудова міст і міських районів привела до збільшення арендної плати і концентрації багатства в одних руках. Встановлено, що в умовах глобальних викликів сучасності високотехнологічні агломерації (мегаміста) виступають осереддям всіх проблем – економічних, с соціальних, культурних, демографічних, еколіогчних. Зроблено спробу розділити міські агломерації на чотири групи міст та виявити їх проблеми. Мегаміста як епіцентри економіки страждають від економічних розколів, розколюються на маленькі зони багатих і великі зони бідних районів. Визначено проблемні питання стратурно-функціональної моделі культурного урбанізму міста, яка направлена на те, щоб вивести глобальний урбанізм на новий рівень технічного, соціального, культурного прогресу і розвитку суспільства. Проанаплізовано перспективи, до яких приведе вирішення проблем глобального урбанізму у контексті розвитку концепції Просвітництва 2.0 і Четвертої промислової революції.
Вирішення проблем глобального урбанізму у контексті розвитку культури, технологій і формування креативного класу
Keywords: global urbanism; urban agglomerations; urban crisis; fourth industrial revolution; creative class; глобальний урбанізм; міські агломерації; урбаністична криза; Четверта промислова революція,; креативний клас